1997
DOI: 10.1088/0305-4470/30/14/001
|View full text |Cite
|
Sign up to set email alerts
|

Logarithmic corrections to gap scaling in random-bond Ising strips

Abstract: Abstract. Numerical results for the first gap of the Lyapunov spectrum of the selfdual random-bond Ising model on strips are analysed. It is shown that finite-width corrections can be fitted very well by an inverse logarithmic form, predicted to hold when the Hamiltonian contains a marginal operator.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…From this we can conclude that the exponent η does not depend on disorder, a result which has been known already 20,21,9,41,11 but without the precision shown above. Note that the correlation length ξ extracted from the ratio of TM eigenvalues (Eq.…”
Section: B the Exponent η And The Ratio γ/νsupporting
confidence: 65%
See 3 more Smart Citations
“…From this we can conclude that the exponent η does not depend on disorder, a result which has been known already 20,21,9,41,11 but without the precision shown above. Note that the correlation length ξ extracted from the ratio of TM eigenvalues (Eq.…”
Section: B the Exponent η And The Ratio γ/νsupporting
confidence: 65%
“…In the off-critical Monte Carlo study of Talapov and Shchur 8 , bond disorder was observed to lead to increased values for the magnetization and susceptibility exponents β and γ, while the behaviour of the specific heat showed good agreement with the double logarithmic form (11). Together with the Rushbrooke equality α + 2β + γ = 2, these findings embody an inconsistency from which the authors concluded that their increased values for β and γ cannot be asymptotic.…”
Section: B Discriminating Between the Scenariosmentioning
confidence: 92%
See 2 more Smart Citations
“…21,23,29,32,34 Nonetheless, for dϭ2 unfrustrated disordered Ising systems they have turned out to be numerically very close, 23,29 at least at the critical point ͑see below for remarks on low-temperature behavior in the present case͒; significant differences arise only in the corrections to scaling, which are relevant for extrapolation to the thermodynamic limit. 34 In Refs. 10,11, the model considered here was studied with the aid of typical correlation lengths typ also calculated on strip geometries, but disregarding corrections to scaling; below, we will comment on some of the differences between our results and theirs.…”
Section: Calculational Methodsmentioning
confidence: 99%